Estudio microbiológico de maceración de arroz (Oryza sativa). II. Determinación de los contenidos de algunos ácidos orgánicos en el líquido de maceración del arroz - Cereda, M.P; Bonassi, I.A; Gil, A.R. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
It is a usual procedure to soak the rice with water, before the husking process, to avoid fragmentation In Brazil, this is usually carried out at room temperature (25— 30°C), inducing off flavors in commercial products. The following organic acids were assayed by gas chronwtography, resulting from fermentation acetic, propionic, butiric, isobutiric, valeric and iwvaleric acids There was a direct relation between the increase of temperature and the amount of acids at 20°C and 30°C, reaching a peak at 40°C and then decreasing at 50°C and 60°C. Better results were obtained with rice soaked at 60°C, with lower acid values (acetic and propionic), that did not induce off flavors.